1.5 Degrees Celsius: The Metamorphosis of the AMERICAN Way of Life, A Transition in Collective Maturation. Issue 5 (18th August 2019) - Fritsch, Pia
Abstract : This article overlays an unorthodox human development model to this moment in American history where the nation will either stay in or rejoin the Paris Agreement or neglect our national environmental responsibility. It argues that this decision mirrors the transition between early and late adolescence. It explores how the societal aspects of love and identity, cultural narrative, ecofeminism, and epistemology must transform for the United States to become a sustainable society. It argues that transitioning into a sustainable way of being represents the metamorphosis of the American way of life like the death and rebirth of the developmental transition.